PENINGKATAN BERFIKIR KRITIS SISWA DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA AUDIO VISUAL DI SEKOLAH DASAR - Miftahhul Jannah; Mufarizuddin; Dwi Viora; Lusi Marleni; M. Syahrul Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low critical thinking skills of students in grade III of UPT SDN 019 Muara Uwai. The failure to achieve critical thinking indicators can be seen from the tendency of students to be passive, difficulty in expressing opinions, and inability to analyze and solve problems logically. This study aims to improve the critical thinking skills of grade III students of UPT SDN 019 Muara Uwai through the application of the Problem Based Learning (PBL) model assisted by audio-visual media. This study uses a Classroom Action Research (CAR) approach which is carried out in two cycles, with stages of planning, implementation, observation, and reflection. The research subjects were 25 students. Data collection instruments include observation sheets, critical thinking ability tests, and documentation. The results of this study can be concluded that students' critical thinking skills have increased in each cycle, as indicated by an increase in the percentage of students in cycle I meeting I reaching (44%), meeting II increasing to (52%), while in cycle II meeting I (76%) and meeting II increasing to (84%). Thus, it can be concluded that the application of the PBL model assisted by audio-visual media can improve students' critical thinking skills on the material of my school rules in class II of UPT SDN 019 Muara Uwai.